Respiratory symptoms among urban traffic policemen in Bangladesh: a cross-sectional study - Parvez Ahmed; Mahim Eaty; Nazmul Alam; Leela Anthony; Nawzia Yasmin (AOSIS, 2022)
Background: There is accumulating evidence that roadside pollution is detrimental to health. Traffic police personnel are exposed to roadside pollution due to the nature of their job and are at risk of adverse health outcomes. Objective:  This study aims to compare the risk of adverse respiratory symptoms in different categories of traffic police including traffic constables, sergeants, and inspectors. Methods: The study population consisted of 369 randomly selected traffic police personnel from the city of Chittagong in Bangladesh. Information on their occupation and respiratory health symptoms were collected. The health outcomes were coughing, coughing sputum, coughing up blood, shortness of breathing, wheezing, and chest pain Result: The risk of coughing [adjusted Odds Ratio (AOR) = 4.469, 95% CI=1.265-15.793], coughing sputum [AOR= 3.687, 95% CI= 1.004 -13.540], coughing up blood [AOR=1.040, 95% CI=0.227-6.162], shortness of breathing [AOR=3.937, 95% CI=1.069-14.500], wheezing [AOR= 2.464, 95% CI= 0.613-9.906] and chest pain with deep breathing [AOR=2.163,95% CI= 0.560-8.349] was higher in traffic constables compared to inspectors. In sergeants odds increased for coughing up blood [AOR=1.102, 95% CI= 0.283-4.286] and wheezing [AOR=1.260, 95% CI= 0.304-5.229]. Conclusion:  There was a substantial difference in the risk of studied respiratory symptoms between different categories of traffic police jobs. Targeted occupational health interventions are recommended.